Families of the world - Tremblay, Helene (New York: Famo Ltda., 1990)
Contents : east asia,peoples republic of China,Japan republic of Korea,southeast asia Brunei,Indonesia,democratic Kampuchea,Lao peoples democratic republic,Malaysia and the pacific,Australia,republic of fiji,Kiribati,Nauru,New Zeland.
Keywords: Family cross cultural studies